Experimental investigation of an unmodified diesel engine operated with ternary fuel. Issue 10 (26th November 2021) - Appavu, Prabhu; Madhavan, Venkata Ramanan; Venu, Harish; Jayaraman, Jayaprabakar
Abstract: The present work focuses on improving the emission and performance parameters of diesel–jatropha biodiesel–pentanol blends. Conventional diesel fuel (D80J20: 80% diesel, 20% jatropha biodiesel) and two blends, D70J20P10 (70% diesel, 20% jatropha biodiesel, 10% pentanol) and D60J20P20 (60% diesel, 20% jatropha biodiesel, 20% pentanol), were used in an unmodified diesel engine in order to study the influence of the various fuel blends on the performance characteristics (brake specific fuel consumption, brake power, and torque) and emissions characteristics (carbon monoxide, nitrogen oxides, and smoke opacity). The experimental values showed that while pentanol inclusion triggered a small reduction in brake power and torque, the exhaust emission parameters of the engine were improved. It is concluded that with 20% pentanol addition in diesel–jatropha biodiesel blends (D60J20P20), the NOx, CO and smoke emissions were reduced by 27.6%, 41.76% and 32.4%, respectively, owing to oxygenated fuel blends and improvement in combustion efficiency.